Socially Communicative Eye Contact and Gender Affect Memory - Lanthier, Sophie N.; Jarick, Michelle; Zhu, Mona J. H.; Byun, Crystal S. J.; Kingstone, Alan (Frontiers in Psychology, 2019)
Because of their value as a socially communicative cue, researchers have strived to understand how the gaze of other people influences a variety of cognitive processes. Recent work in social attention suggests that the use of images of people in laboratory studies, as a substitute for real people, may not effectively test socially communicative aspects of eye gaze. As attention affects many other cognitive processes, it is likely that social attention between real individuals could also affect other cognitive processes, such as memory. However, from previous work alone, it is unclear whether, and if so how, socially communicative eye gaze affects memory. The present studies test the assumption that socially communicative aspects of eye gaze may impact memory by manipulating the eye gaze of a live speaker in the context of a traditional recognition paradigm used frequently in the laboratory. A female (Exp. 1) or male (Exp. 2) investigator read words aloud and varied whether eye contact was, or was not, made with a participant. With both female and male investigators, eye contact improved word recognition only for female participants and hindered word recognition in male participants. When a female investigator prolonged their eye contact (Exp. 3) to provide a longer opportunity to both observe and process the investigator’s eye gaze, the results replicated the findings from Exp. 1 and Exp. 2. The findings from Exp. 1-3 suggest that females interpret and use the investigator’s eye gaze differently than males. When key aspects from the previous experiments were replicated in a non-communicative situation (i.e., when a video of a speaker is used instead of a live speaker; Exp. 4), the memory effects observed previously in response to eye gaze were eliminated. Together, these studies suggest that it is the socially communicative aspects of eye gaze from a real person that influence memory. The findings reveal the importance of using social cues that are communicative in nature (e.g., real people) when studying the relationship between social attention and memory.